Adultos com deficiência intelectual incluídos na educação de jovens e adultos : apontamentos necessários sobre adultez, inclusão e aprendizagem - Bins, Katiuscha Lara Genro (2013)
Every human being is a collection of their biological and social context and so unique. I think that human diversity is still a little respected in educational environment especially when the characteristic of the difference is of the deficiency. The school is not yet prepared to work with the differences. Keeps on seeking and demanding homogenizations such as the students as learning. The EJA, even as a teaching modality of education that has basic inclusive assumptions, still can not work with and from the differences. In this educational universe are included adults with intellectual disabilities. The Adults with intellectual disabilities are attending adult education, but, in most cases, are not able to handle the contents and requirements that the traditional teaching still requires and demands. Many times these students stay in school for years, the same level of education, without improving. This way, their presence in the EJA is a challenge for teachers who need to respond to their demands and ensure a quality education. I believe that it is necessary to (re) congnize their knowledge and their potentialities, get to know how their learning work and hence its development within the school environment. While noticing some changes have already occurred, such as the right of access to regular educational system, it is necessary to go further and also ensure them the right to educational opportunities and concrete practical learning. I take this research a learning perspective throughout life, education as a right for all human beings, being these the principles that move me and that impel me to reflect and discuss about intellectually disabled adults included in EJA. Having thus main focus the person with intellectual disabilities included in EJA, I structured aspects to be studied and analyzed: his adulthood, because they are still seen and treated as "eternal children" and we must recognize them as adults; inclusion because ponder that they were included, more for law demandings than by beliefs and attitudes really inclusive; and learning, in order to (re) congnize who is the adult learner with intellectual disabilities, their organic deficits, cognitive and social, and especially what are their potentialities , respecting and using them in the teaching-learning strategies, because only then can be possible to think about strategies and opportunities for learning and comprehensive training. I conclude with the adequacy and inadequacy of education for youth and adults for people with intellectual disabilities, weaving a web of considerations about positive and negative aspects. By approaching them I intend to raise discussions and point out elements that I evaluate, need to be rethought, others who need to leave the theoretical universe and become practical realities, possible to be done. The research was conducted in a municipal school of Youth and Adult Education in Porto Alegre. I searched through the data obtained by observation, document analysis and semi-structured interviews, to describe the youth and adults reality of the education of with intellectual disabilities included in the EJA. The assumptions that guided this research are qualitative.